2017
DOI: 10.3389/fmicb.2017.02570
|View full text |Cite
|
Sign up to set email alerts
|

Autoinducer-2 Quorum Sensing Contributes to Regulation of Microcin PDI in Escherichia coli

Abstract: The Escherichia coli quorum sensing (QS) signal molecule, autoinducer-2 (AI-2), reaches its maximum concentration during mid-to-late growth phase after which it quickly degrades during stationary phase. This pattern of AI-2 concentration coincides with the up- then down-regulation of a recently described microcin PDI (mccPDI) effector protein (McpM). To determine if there is a functional relationship between these systems, a prototypical mccPDI-expressing strain of E. coli 25 was used to generate ΔluxS, ΔlsrAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 62 publications
1
16
0
Order By: Relevance
“…Data from multiple assays from the present study are consistent with the conclusion that the MccPDI precursor protein McpM kills susceptible strains via membrane disruption, and experiments here and elsewhere confirm that naturally susceptible strains are widespread (6)(7)(8)24). OmpF is the key ligand for susceptibility (8,42), but other genes have been identified that are requisite for susceptibility to MccPDI (ompR, atpA, atpF, atpE, atpH, dsbA, and dsbB [8]).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Data from multiple assays from the present study are consistent with the conclusion that the MccPDI precursor protein McpM kills susceptible strains via membrane disruption, and experiments here and elsewhere confirm that naturally susceptible strains are widespread (6)(7)(8)24). OmpF is the key ligand for susceptibility (8,42), but other genes have been identified that are requisite for susceptibility to MccPDI (ompR, atpA, atpF, atpE, atpH, dsbA, and dsbB [8]).…”
Section: Discussionsupporting
confidence: 88%
“…Microcin PDI inhibits Shigella strains and UTI E. coli strains. Previously validated coculture competition assays (5)(6)(7)(8)24) were employed to examine the sensitivity of the target bacteria to MccPDI. The coculture competition assays were conducted with E. coli strain 25 (MccPDI producer), six Shigella strains, and nine UTI E. coli strains that were resistant to between one and four classes of antibiotics ( Table 2 and Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tetracycline resistance genes, in contrast, were elevated in the wild without an attendant significant upregulation of resistance. This pattern raises the possibility that the antibiotics pathways upregulated in captivity may be adapted for competition and virulence factor regulation (Balasubramanian et al 2011), whereas the pathways upregulated in the wild may play more of a quorum sensing role (Lu 2006).…”
Section: Discussionmentioning
confidence: 99%
“…One of the earliest documented examples is the production of the antibiotic carbapenem in the plant pathogen Pectobacterium carotovorum (McGowan et al, 1995). Later reports have also documented quorum sensing regulation of carbapenem production in other bacteria, such as Serratia (Thomson et al, 2000), as well as quorum sensingregulated production of other antibacterials, including hydrogen cyanide (Pessi and Haas, 2000), bacteriocins (van der Ploeg, 2005), polyketide or peptide antibiotics (Duerkop et al, 2009) and microcin (Lu et al, 2017).…”
Section: Does Quorum Sensing Affect Pathogen Fitness In a Host?mentioning
confidence: 99%